Bone marrow necrosis in acute leukemia: Clinical characteristic and outcome. Issue 9 (27th July 2015) - Badar, Talha; Shetty, Aditya; Bueso‐Ramos, Carlos; Cortes, Jorge; Konopleva, Marina; Borthakur, Gautam; Pierce, Sherry; Huang, Xuelin; Chen, Hsiang‐Chun; Kadia, Tapan; Daver, Naval; Dinardo, Courtney; et al.
<x xml:space="preserve">Abstract</x> Bone marrow necrosis (BMN) is characterized by infarction of the medullary stroma, leading to marrow necrosis with preserved cortical bone. In reported small series, BMN in hematological malignancies is associated with poor prognosis. We sought to find the impact of BMN on clinical outcome in a relatively larger cohort of patients with acute leukemias. Overall we evaluated 1, 691 patients; 1, 051 with acute myeloid leukemia (AML) and 640 with acute lymphocytic leukemia referred to our institution between 2002 and 2013. Patients with AML and acute lymphoblastic leukemia (ALL) were evaluated separately to determine the incidence of BMN, associated clinical features and its prognostic significance. At initial diagnosis, BMN was observed in 25 (2.4%) patients with AML and 20 (3.2%) patients with ALL. In AML, BMN was significantly associated with French–American–British AML M5 morphology (32% vs. 10%, P = 0.002). The complete remission (CR) rate in AML with and without BMN was 32% and 59% respectively (P = 0.008). Likewise, CR rate in ALL with BMN was also inferior, 70% vs. 92% (P = 0.005). The median overall survival (OS) in AML with BMN was significantly poorer, 3.7 months compared to 14 months without BMN (P = 0.003). Similarly, the median OS in ALL with and without BMN was 61.7 and 72 months respectively (P = 0.33). BMN is not a rare entity in AML and ALL, but is infrequent. BMN in AML and in ALL is suggestive of inferior response and poor prognosis. Am. J. Hematol. 90:769–773, 2015. © 2015 Wiley Periodicals, Inc.